Preparing community pharmacists for a role in mental health: An evaluation of accredited Australian pharmacy programs - Mey, A.; Hattingh, H. Laetitia; Davey, A.; Knox, K.; Fejzic, J.; Wheeler, A. (Elsevier Inc., 2015)
Background: Australian community pharmacists are well placed to provide medication-related support and contribute to optimization of outcomes for mental health consumers and their caregivers. However, little is known about the actual competencies of community pharmacists to provide this care. To determine how graduates are being prepared to competently assist mental health consumers and their caregivers, an exploration of the mental health content of university pharmacy programs that set the foundation for pharmacists' professional roles is needed. Aim: To investigate the mental health content of accredited Australian pharmacy qualifying programs. Method: A review of publically available online profile information for accredited degree programs was conducted, and program coordinators from the 18 accredited pharmacy degree programs providers in Australia were surveyed. Results: Mental health education is embedded in core subjects such as pharmacology, pharmacotherapy, and pharmacy practice. Multiple options are employed to deliver mental health teaching, including lectures, workshops, and experiential learning. However, while education is intended to align with pharmacists' expected level of professional competencies, there is a lack of national standardized outcome-based competency criteria for new graduates and wide-ranging inter-program variations were evident. Conclusion: A lack of standardized content in pharmacy qualifying programs that underpin pharmacists' mental health knowledge and skills might result in variations to practice competencies. Further work is needed to determine how variations impact the way pharmacists deliver care to mental health consumers and their caregivers.